MICROPROPAGATION AND ASSESSMENT OF GENETIC FIDELITY OF REGENERATE BY RAPD MARKERS OF SOLANUM NIGRUM - Farqad M. K. ALdabbagh; Iqbal H. M. AL_Zaidi; Magidah A. K. ALshamari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
In vitro propagation approach has been adopted for micropropagation and conservation of Solanum nigrum (black nightshade) to guarantee its sustainable phyto-industry and research availability. Within 1 month, in vitro shoot differentiated was accomplished by culturing shoot tip, nodal segment, and leaf on MS medium enriched with various BA (Benzyl Adenine) concentrations. A significant difference was observed with shoot tips compared with nodal explants and leaf at the shoot induction percentage and mean number of shoot per explant. The highest percentage of shoot induction (100%) and average number of micro shoot per shoo tip (9.200 shoot) were recorded on MS medium fortified with 1 mg/l BA. The findings showed that a satisfactory rooting percentage (100%) was recorded when I mg/l IBA (Indole Butyric Acid) added to half MS medium with an average number of roots (2.600) root/shoot, a mean root length is 8.600cm. rooted plantlets could be successfully acclimatized in the shade house with 100% survival rate. The genetic stability of the micropropagated plants investigated by the RAPD markers indicated monomorphic and true to type when compare with the original plant.